2009
DOI: 10.3855/jidc.311
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-transmissible infections among blood donors in Kathmandu, Nepal

Abstract: Background: Screening of transfusion-transmissible infections (TTIs) among blood donors can be a cost-effective approach to monitor the prevalence, distribution, and trends of the infections among healthy-looking individuals. The study aimed to determine the seroprevalence of four TTIs, human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis, among blood donors in Kathmandu, Nepal. Methodology: A total of 21,716 units of blood were tested for the presence of anti-HIV 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
56
15
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 13 publications
14
56
15
4
Order By: Relevance
“…This number showed a lower prevalence compared with other studies done in Mozambique (18.7%) [11], East Sudan (13%) [12], Cameroon (13.7%) [13], in Gondar Ethiopia (18.5%) [14]. However, the present study showed the prevalence of TTIs was high compared with a study done in Nepal (1.7%) [15] and in India (0.93%) [16]. The prevalence/epidemiology of TTIs varies among countries and settings.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This number showed a lower prevalence compared with other studies done in Mozambique (18.7%) [11], East Sudan (13%) [12], Cameroon (13.7%) [13], in Gondar Ethiopia (18.5%) [14]. However, the present study showed the prevalence of TTIs was high compared with a study done in Nepal (1.7%) [15] and in India (0.93%) [16]. The prevalence/epidemiology of TTIs varies among countries and settings.…”
Section: Discussioncontrasting
confidence: 56%
“…This study showed that, although not statistically associated, HBV was more common in males 5% (13), married 6.3% (2), urban population 4.2% (15), the 18-24 age group 4.5% (15), and in replacement donors 9.7% (3), which is different from the prevalence of HIV (Table 3). In addition, many of these study participants were volunteer donors, who mainly were males 67.5% (232) …”
Section: Resultsmentioning
confidence: 50%
“…[12][13][14][15][16][17] Studies conducted by Khedmatet al 18 (0.003%) in Iran and Ahmadet al 19 (0.008%) in Bangladesh showed lesser prevalence of HIV while variable results of 0.12%, 0.15% and 0.11%have also been reported in various other studies conducted in Nepal, China and Pakistan respevtively. 20,21,22 Prevalence of HBsAg in our blood donor population was 2.1% which was contrary to the findings of other studies. 12,14,16,[18][19][20][21] Studies by Chaudhary et al(1.93%) in western UP, Naskar et al (1.75%) in northern India, andZameeret al (2.9%) in Pakistan showed similar findings when compared to the present sudy.…”
Section: Resultscontrasting
confidence: 57%
“…20,21,22 Prevalence of HBsAg in our blood donor population was 2.1% which was contrary to the findings of other studies. 12,14,16,[18][19][20][21] Studies by Chaudhary et al(1.93%) in western UP, Naskar et al (1.75%) in northern India, andZameeret al (2.9%) in Pakistan showed similar findings when compared to the present sudy. 13,15,22 Detection of the IgM class of antibodies to the hepatitis B core antigen (Anti HBc -IgM) as an adjuvant marker can be used to confirm recent infection of HBV so that the higher prevalence of HBsAg among blood donors can be reduced.…”
Section: Resultscontrasting
confidence: 57%
“…The findings of the present study were similar to the study conducted by Shrestha et al, 2009 (HIV-0.12%, HBsAg-0.46%). 8 However, the seroprevalence of HIV was 4.5% and HBV-8.2% in Ethiopia during 2008. 9 In addition, the HIV and HBsAg seroprevalence was found to be 0.69% and 4.61% respectively in Thailand, 2002.…”
Section: Discussionmentioning
confidence: 99%